IL-4 Is a Key Requirement for IL-4- and IL-4/IL-13-Expressing CD4 Th2 Subsets in Lung and Skin - Prout, Melanie Sarah; Kyle, Ryan L.; Ronchese, Franca; Le Gros, Graham (Frontiers in Immunology, 2018)
Although IL-4 is long associated with CD4 Th2 immune responses, its role in Th2 subset development in non-lymphoid tissues is less clear. We sought to better define IL-4’s role in CD4 Th2 responses by using transgenic mice that express a dual IL-4 AmCyan/IL-13 DsRed (IL-4AC/IL-13DR) fluorescent reporter on an IL-4-sufficient or IL-4 deficient background. Using primary Th2 immune response models against HDM or N. brasiliensis allergens we examined the requirement for IL-4 by each of the defined Th2 subsets in the antigen draining lymph node, skin and lung tissues. In the lymph node, a CXCR5+PD1+ Tfh and a CXCR5loPD1lo Th2 subset could be detected that expressed only IL-4AC but no IL-13DR. The number of IL-4AC+ Tfh cells was not affected by IL-4 deficiency whereas the number of IL-4AC+ Th2 cells was significantly reduced. In the non-lymphoid dermal or lung tissues of allergen primed or N. brasiliensis infected mice three strikingly distinct T cell subsets could be detected that were either IL-4AC, or IL-4AC/IL-13DR, or IL-13DR CD4. The IL-4 and IL-4/IL-13 expressing subsets were significantly reduced in IL-4 deficient mice, while the numbers of IL-13 expressing CD4 T cells were not affected by IL-4 deficiency indicating that other factors can play a role in directing the development of this Th2 subtype. Taken together these data indicate that the appearance of IL-4 expressing Tfh cells in the lymph node is not dependent on IL-4 while the appearance of IL-4 expressing Th2 subsets in the lymph node and IL-4 , IL-4/IL-13 expressing Th2 subsets in skin and lung tissues of antigen primed mice is significantly IL-4-dependent.